The Kenya Surgical Capacity Study: An Audit of Surgical Equipment/Infrastructure in Level 4 Public Hospitals - Sara Chaker; Jaymie Ang Henry; Ya-Ching Hung; Mariam Saad; Elizabeth Slater; SriGita Krishna Madiraju; Patrick Mwai; Pankaj Jani; Kevin Lan; Peter Nthumba (The Annals of African Surgery)
Background: Access to surgical equipment is critical to providing safe and equitable operative care. This is the first nationwide study to provide data on the availability of surgical equipment in Kenya. Methods: This cross-sectional study collected data from May to July 2018 on the availability of non-pharmaceutical equipment, patient care, intra-operative, and anesthesia supplies in level 4 hospitals. Information regarding infrastructure such as the number of functional operating rooms, sterilization capacity, and sources of water and electricity was also collected. Results: The availability of intra-operative and anesthesia equipment was 44.5% and 47%, respectively. Nearly 60% of facilities had general patient care supplies. Over 80% of the facilities had running water in maternity wards (83.1%). Sterilization equipment was present in about half of the facilities (range: 42.6–68.3%). Additionally, 79.1% had a generator as a backup source of electricity. Only 35% of facilities always had an X-ray on-site, and 52.6% of the facilities obtained blood from the national or a regional center. Conclusion: This study provides data on the availability of surgical equipment and infrastructure in level 4 hospitals in Kenya. Availability of radiology services and blood supply was lower than that in other sub-Saharan African countries, highlighting the need for improved surgical care resources in these community-based facilities.